(untitled) (Web of Teachers: Inderscience Research, 2023)
This article examines the role of comparative study, analysis of the properties of chemical elements in the teaching of chemistry. He focuses on analyzing the diagonal similarity of the elements. This approach is based on the promotion of scientific literacy of students.